Implementation of Fuzzy Logic in Stabilizing Temperature and Humidity in Freeze Dryers for Dried Apple - Ghassan Rafananda Raja Harahap; Shafira Fayza Dewani Sudiro; Rayna Suci Alifah; Salsabila Salsabila; Ade Trisna Iswanda; Xaviera Yasmin Azahra; Ghina Khairunnisa Putri; Syifa Az Zahra; Hidayat Faiz Sanjaya; Izharul Haq Ar Rafi; Aisyah Sakha Damarjati; Enjela Rahmawati; Nanda Octavia; Ester Angeline; Muhammad Danang Mukti Darmawan; Fiqri Nurfadillah; Mrr Lukie Trianawati (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
Freeze drying is a process to remove water from a material by sublimation, in the form of ice under low pressure. This process is used to stabilize food, and pharmaceutical products. During the process, the dried product maintains its quality, including biological, nutritional, and sensory properties, because freezing the water within the material before lyophilization prevents chemical, biochemical, and microbiological reactions. The aim of this research is to determine the optimal temperature and time to produce good products in the freeze drying process. The method used for this article is the literature study and observation method. This research uses manual calculations which are then implemented in a control system using a fuzzy logic algorithm in the Matlab application. In conclusion, both the manual calculation results and the matlab calculations that have been conducted are the same, which confirms the accuracy and validity of the preceding calculations.